The Influence Of Product Quality And Religius On Customer Decisions In Choosing Sharia Insurance At PT. Sun Life Financial Medan City Branch - Aulia, M.; Nurbaiti, Nurbaiti; Syahriza, Rahmi (Moneter: Jurnal Keuangan dan Perbankan, 2025)
The purpose of this research is to determine the influence of product quality implemented by the company and the level of religiosity of customers on the decision to choose sharia insurance at PT Sun Life Medan City Branch. From this, the author is interested in research entitled The Influence of Product Quality and Religiosity on customers’ decisions in choosing sharia insurance at PT Sun Life Medan City Branch. In this research, quantitative methods are used. Quantitative research is a process of finding knowledge that uses data in the form of numbers as a tool to analyze information about what you want to know. This research uses statistical data analysis with the final result of the research being the verification of a theory or hypothesis to be accepted or rejected. This research uses multiple regression analysis methods to see the influence of independent variables, namely independent variables only. The research results show that there is a significant influence between product quality on customer decisions in choosing insurance at PT. Sun Life Financial Medan Branch. There is a significant influence between religiosity on customers’ decisions in choosing insurance at PT. Sun Life Financial Medan Branch. Together, product quality and religiosity can have a significant influence on customers’ decisions about having insurance at PT. Sun Life Financial Medan Branch.